Some new estimates for Fej´er type inequalities in quantum analysis - BRAHIM, Kamel; RIAHI, Latifa; AWAN , Muhammad Uzair (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
In this paper we derive some new quantum estimates of Fej´er type inequalities which involve Riemann type of quantum integrals via some classes of convex functions. We also discuss some special cases which can be deduced from the main results of this paper. Mathematics Subject Classification (2010): 26D15, 26A51.